Mechanistic optimization of inavolisib combined with CDK4/6 inhibitors in the treatment of PIK3CA-mutated breast tumors - Zhu, Rongyu; Zhang, Haixin; Zhang, Fuli (Frontiers in Immunology, 2025)
PIK3CA mutations are common oncogenic mutations in breast cancer, and abnormal activation of the PI3K/AKT/mTOR pathway is a key mechanism underlying tumorigenesis and drug resistance. Inavolisib is a selective PI3Kα inhibitor approved for the treatment of hormone receptor-positive breast cancer with PIK3CA mutations. CDK4/6 inhibitors (such as palbociclib and ribociclib) block the transition from the G1 to S phase of the cell cycle and have become standard treatment for hormone receptor-positive breast cancer. Both agents exhibit resistance issues when used as monotherapy, particularly in the context of PIK3CA mutations. Studies have shown that the combination of CDK4/6 inhibitors with PI3K inhibitors (such as inavolisib) significantly enhances antitumor efficacy. Additionally, the combination therapy effectively inhibits tumor cell proliferation and induces apoptosis. In preclinical studies, this combination strategy demonstrated significant antitumor activity in various PIK3CA-mutated xenograft models. Although clinical trials (e.g., NCT04191499) are exploring the potential of inavolisib combined with CDK4/6 inhibitors, challenges remain, including toxicity management, biomarker selection, and optimizing dosing regimens to enhance efficacy and reduce side effects. This review synthesizes preclinical and clinical evidence on the mechanistic optimization of inavolisib combined with CDK4/6 inhibitors for PIK3CA-mutated breast cancer. It covers molecular mechanisms, synergistic effects, resistance strategies, biomarkers, and future directions, with an emphasis on immunological implications. The scope is limited to HR+/HER2-negative subtypes, excluding other cancers or non-PI3K-targeted therapies, to provide a focused foundation for translational immunology in oncology.